Neural Processes of Proactive and Reactive Controls Modulated by Motor-Skill Experiences - Yu, Qiuhua; Chau, Bolton K. H.; Lam, Bess Y. H.; Wong, Alex W. K.; Peng, Jiaxin; Chan, Chetwyn C. H. (Frontiers in Human Neuroscience, 2019)
This study investigated the experience of open and closed motor skills on modulating proactive and reactive control processes in task switching. Fifty-four participants who were open-skilled (n = 18) or closed-skilled athletes (n = 18) or non-athletic adults (n= 18) completed a cued task-switching paradigm task. This task tapped into proactive or reactive controls of executive functions under different validity conditions. Electroencephalograms of the participants were captured during the task. In the 100% validity condition, the open-skilled participants showed significantly lower switch cost of response time than the closed-skilled and control participants. Results showed that the open-skilled participants had less positive-going parietal cue-locked P3 in the switch than repeat trials. Participants in the control group showed more positive-going cue-locked P3 in the switch than repeat trials, whereas the closed-skilled participants had no significant differences between the two types of trials. In the 50% validity condition, the open- and closed-skilled participants had less switch cost of response time than the control participants. Participants in the open- and closed-skilled groups showed less positive-going parietal stimulus-locked P3 in the switch than repeat trials, which was not the case for those in the control group. Our findings confirm the dissociation between proactive and reactive controls in relation to their modulations by the different motor-skill experiences. Both proactive and reactive controls of executive functions could be strengthened by exposing individuals to anticipatory or non-anticipatory enriched environments, suggesting proactive and reactive controls involved in motor-skill development seem to be transferable to domain-general executive functions.